ANALYSIS OF THE IMPLEMENTATION OF SHARIA ACCOUNTING BASED ON SFAS 102 ON MURABAHAH FINANCING IN BMT BARI'USSALAM BATAM - Abdul Wachid (LP2M-Institut Agama Islam Abdullah Said Batam, 2022)
This research aimed to analyze the recognition and measurement, presentation and disclosure of murabaha transaction in accordance with SFAS 102 at BMT Bari’ussalam Batam. It was field research with qualitative approach. The methods of data collection were interviews and documentation. The results of this research indicated that the BMT recognizing inventories which should not be done because the practice is murabahah not purchase-based murabaha transactions. BMT has been preparing financial statements Balance Sheet, but the value of the loss reserve accounts Murabahah cannot be seen. In profit/ loss reports, costs of murabaha receivables impairment losses cannot be seen because it is not recognized/recorded in the general journal. BMT has revealed matters related to murabaha transactions, including the acquisition cost of murabaha asset; booking appointment in murabaha based on the order as an obligation or not, while the non-commercial financial reports have been prepared for internal purposes of BMT not to publish.